Penatalaksanaan Radioterapi Kanker Paru-paru dengan Teknik Intensity Modulated Radiation Therapy (IMRT) : Lung Cancer Radiotherapy Management with Intensity Modulated Radiation Therapy (IMRT) Technique - Muhammad Raihan; Risska Hasanah; Dewi Dewi; Ratu Sabrina; Dwi Rangga pramana; Rasya Alfattah; Anisa Dwi Agustin; Intan Maulina (Elektriese: Jurnal Sains dan Teknologi Elektro, 2026)
Lung cancer is one of the leading causes of cancer death worldwide, with mortality rates continuing to rise annually. According to WHO data in 2021, approximately 1.8 million deaths were caused by lung cancer, making it a significant global health problem. In Indonesia, the prevalence of lung cancer is also increasing, especially in the elderly and among active and passive smokers. Radiotherapy is one of the main modalities in the management of lung cancer, especially for patients who cannot undergo surgery. With technological advances, Intensity-Modulated Radiation Therapy (IMRT) was developed to improve the precision of radiation dose delivery while still protecting healthy tissue around the tumor. This study aims to systematically review the literature on the effectiveness and safety of Intensity-Modulated Radiotherapy (IMRT) compared with conventional techniques, such as Three-Dimensional Conformal Radiotherapy (3D-CRT). The method used was a Systematic Literature Review (SLR) following the PRISMA 2020 guidelines for international articles published in the last five years (2019–2024). Research results show that IMRT can reduce radiation doses to vital organs such as the heart, contralateral lung, and spinal cord, while reducing cardiopulmonary toxicity without compromising tumor control. IMRT derivative techniques such as Volumetric Modulated Arc Therapy (VMAT) and Simultaneous Integrated Boost IMRT (SIB-IMRT) have also been shown to improve radiation accuracy and patient quality of life. IMRT is an important innovation in radiation oncology that is effective, safe, and has the potential to become the gold standard for lung cancer radiotherapy in the future.